Investment, Tourism, and Creative Industry: a Strategic of Indonesian Special Economic Zones in Singhasari - Putra Sri Sentanu*, I Gede Eko; Prabowo, Ardian; Haryono, Bambang Santoso (Riwayat: Educational Journal of History and Humanities, 2023)
To accelerate nati onal economic development, the government needs to increase investment by preparing areas with economic and geostrategic advantages. The Singhasari Special Economic Zone (SEZ) is ready to maximize industrial, export, import, and other economic activities with high creative economic value. This research aims to evaluate the strategy for Singasari SEZ by maximizing potential resource development capital, especially the development of digital ecosystems and the creative economy. The geostrategic advantage of the area owned by Singhasari is the tourism sector with the theme of heritage and historical tourism. This study uses qualitative methods through SWOT analysis. The analysis is carried out to maximize the role of strength factors and exploit opportunities to minimize weaknesses and reduce the impact of threats that arise and must be faced in SEZ Singhasari, Malang Regency. The findings of this study indicate that the Singhasari SEZ has been running according to the initial planning roadmap as a place for collaboration between several parties in improving the tourism sector and the creative economy, but, in the process, it still needs help accessing funding. Several strategies need to be implemented to maximize the program, such as re-planning or refocusing factors in the tourism and creative industries, digitization, digital talent, investment, and collaboration between stakeholders in the Singhasari SEZ the key to strengthening the Singhasari SEZ further.